The puzzle of solar lift irrigation in Nepal’s mid-hills - Shrestha, Shisher; Neupane, Nilhari; Joshi, Ritavrat; Khadka, Manohara (CGIAR, 2023)
The mid-hills of Nepal account for 68% of the country’s total area[1] and 56% of its arable land. Ranging in altitude from 610m to 4,876m, there are many small pockets of micro-irrigation that have the potential for high-value crop cultivation. However, almost a third of irrigable land here remains rainfed[2] and studies indicate an increase in fallow land due to a lack of year-round irrigation infrastructure and decrease in agricultural workforce. A recent census found that several mid-hill districts have experienced negative population growth over the past decade, largely due to water scarcity, poverty, economic migration, and food insecurity.